Seasonal influence, enteropathogenic microbial load and diarrhoeal enigma in the Gangetic Delta, India: Present scenario and health implications - Suvajit Saha; Madhumanti Halder; Subham Mookerjee; Anup Palit (Elsevier, 2019)
Background: Environmental diarrheagenic enteropathogens, effect of surrounding attributes and disease dynamicity remains far from being conclusively explored. Population flux, poor sanitation and hygienic practice poses potential health threat in diarrhoea endemic tropical countries like India. We aim to identify environmental attributes, seasonality of water-borne enteropathogens and health risk assessment off the river Ganges. Methods: A yearlong sampling data generated from three sites on either sides of the River was analysed and implications have been reported. Immediately after sample collection, physico chemical and bacterial indices were measured at the sampling site and laboratory respectively, followed by further statistical analysis of the findings. Results: Annual variation of physico-chemical indices viz., temperature 18 °C-36 °C, pH 7.49-8.67, conductivity 215-468 μS/cm and turbidity 25.6-593 NTU was recorded in the riverine water samples. High temperature and turbidity were recorded in the summer and monsoon at all sites. High bacterial dispersion has been positively correlated with turbidity and temperature variation (P < 0.01; P < 0.1) as we report TBC 103-105 CFU/ml, TCC 103-104 CFU/ml and CVC 4-212 CFU/ml, with higher distribution in the monsoon and reverse in the winter. This suggests that the bacterial pool proliferates at higher temperature whereas turbidity enhances their survival providing the substratum for the bacterial pool. CVC could be positively correlated with conductivity which implies that ionic content of water augments the Vibrio load. Adaptive capability of Vibrios to sustain in very low saline riverine setting seems to be assisted by turbid water coupled with nutrient rich organic matter. Conclusion: Our present work establishes the interplay of seasonal variants on the dynamicity of enteropathogenic bacteria in flowing aquatic ecosystem. It also categorises the existing microbial threats in the Ganga River to help monitor the conventional as well as emerging diarrhoeal pathogens to reduce diarrheal recurrences. Keywords: Seasonality, Hydrology, Physico-chemical parameters, Enteropathogens, Community health